Facile in-situ electrochemical fabrication of highly efficient nickel hydroxide-iron hydroxide/graphene hybrid for oxygen evolution reaction. (22nd March 2022) - Zhao, Man; Xue, Shoufeng; Xiao, He; Gao, Jianru; Cheng, Xiaoru; Jing, Yanying; Jia, Jianfeng; Wu, Haishun
Abstract: Oxygen evolution reaction (OER) is an essential process in energy conversion and storage, especially in water electrolysis, while developing active and low-cost catalysts is the key to maximizing O2 production. Here a facile three-electrode electrolysis system is firstly applied to synthesize nickel hydroxide-iron hydroxide/graphene hybrid. To fully utilize the electrical energy and simplify the catalyst synthesis, we made graphite exfoliated into graphene at the cathode and nickel-iron hydroxide synthesized at the anode simultaneously. The best electrocatalytic performance of Ni–Fe/G for OER shows an overpotential of 280 mV (without iR compensation) at 10 mA cm −2, superior to commercial RuO2 (341 mV). Results show that the introduction of Fe in Ni–Fe/G not only converts part of α-Ni(OH)2 into more active β-Ni(OH)2, but promotes the electric conductivity and electrochemically active surface area (ECSA) of the obtained Ni–Fe/G, therefore Ni–Fe/G shows the superior OER performance. The OER activity of Ni–Fe/G can be further adjusted by experiment conditions including electrolysis time and electrolyte concentration. This work provides a novel and facile method for highly efficient OER via engineering the non-noble metal hydroxide/graphene hybrid. Graphical abstract: Electrosynthesized nickel hydroxide-iron hydroxide/graphene hybrid by a three-electrode electrolysis system for efficient oxygen evolution reaction. Image 1 Highlights: A facile electrosynthesis method is designed for synthesis of Ni–Fe/graphene hybrid. This obtained hybrid shows superior electrocatalytic activity toward OER to RuO2 . Promotion of incorporated Fe to Ni hydroxide on OER performance is revealed. OER activity of Ni–Fe/G can be adjusted by electrolysis conditions.